2009
DOI: 10.1007/s11113-009-9167-0
|View full text |Cite
|
Sign up to set email alerts
|

Family Contexts and Schooling Disruption among Orphans in Post-Genocide Rwanda

Abstract: This study examines the relationship between orphan status and schooling disruption in post-genocide Rwanda. The results indicate that while non-orphans have more favorable schooling outcomes in two-parent than in single-parent families, the reverse is true among Rwandan orphans. In single-mother households, paternal orphans, i.e. orphans with only a living mother, have better outcomes than their orphan and non-orphan counterparts. In contrast, paternal orphans have worse outcomes than other children in two-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 59 publications
(66 reference statements)
1
10
0
Order By: Relevance
“…There is evidence that orphans and foster children are less likely to be enrolled in school than children who live with their biological parents (see [28,29]). Thomas [30] confirms this finding for Rwanda and also reports that the extent of schooling deprivation of orphans depends on their family relation to the caretakers, the household type (single or double headed), and the gender of the household head. These relationships are rather complex.…”
Section: Barriers To and Inducements For Primary School Attendancesupporting
confidence: 53%
See 1 more Smart Citation
“…There is evidence that orphans and foster children are less likely to be enrolled in school than children who live with their biological parents (see [28,29]). Thomas [30] confirms this finding for Rwanda and also reports that the extent of schooling deprivation of orphans depends on their family relation to the caretakers, the household type (single or double headed), and the gender of the household head. These relationships are rather complex.…”
Section: Barriers To and Inducements For Primary School Attendancesupporting
confidence: 53%
“…Orphans, for instance, are more disadvantaged in a household headed by a couple than in a single-headed household, contrary to the situation of children who live with natural parents. Taking care of children below primary school age is supposed to be an impediment to the school enrolment of particularly full and maternal orphans (see [30]). Case and Ardington [31], Evans and Miguel [32] also concluded that there is a substantial decrease in school participation after the death of a parent and that the death of the mother is more detrimental than that of a father, as male-headed household will more often rely on children for household chores.…”
Section: Barriers To and Inducements For Primary School Attendancementioning
confidence: 99%
“…In line with prior research that employs Hamilton's rule to study the education of orphans in other sub-Saharan Africa countries (e.g., Case et al 2004;Kobiane et al 2005;Thomas 2010), our research examines whether Hamilton's rule is applicable to the schooling of orphans in Nigeria. Specifically, we investigate whether orphans who have a close genetic relationship with the household head, such as grandchildren, siblings, and nieces/nephews, experience a schooling advantage over those who have a more distant relationship or none at all.…”
Section: Introductionmentioning
confidence: 97%
“…A growing body of evidence indicates that parental death is negatively associated with child and adolescent outcomes. Studies point to orphan disadvantage in the realms of schooling, mental and physical health, and sexual risk behavior (e.g., Birdthistle et al 2008; Case, Paxson, and Ableidinger 2004; Miller et al 2007; Nyamukapa et al 2008; Thomas 2009). Research also indicates differences in association by orphan type, with results from recent longitudinal studies usually suggesting a causal effect of orphanhood for maternal but not paternal orphans (Ainsworth, Beegle, and Koda 2005; Beegle, De Weerdt, and Dercon 2010; Case and Ardington 2006; Evans and Miguel 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Results from longitudinal studies indicate that though economic resources are consequential to orphans’ differential disadvantage, a gap between maternal orphans and non-orphans persists over and above economic controls (Beegle, De Weerdt, and Dercon 2010; Case and Ardington 2006; Evans and Miguel 2007). Related scholarship also indicates that maternal orphans are less likely than paternal orphans to live with a surviving parent (Beegle et al 2010; Case, Paxson, and Ableidinger 2004; Hosegood et al 2007a; Thomas 2009), and that children may experience differential schooling and health outcomes based on degree of relatedness to their caregivers (Bishai et al 2003; Case, Paxson, and Ableidinger 2004; Thomas 2009). To date, however, little in-depth work has documented the content of caregiving relationships giving rise to these differential outcomes between children, beyond the observation that in households with both biological and non-biological children, biological children may be favored (Ansell and Young 2004; Case, Paxson, and Ableidinger 2004; Nyamukapa and Gregson 2005; Thomas 2009).…”
Section: Introductionmentioning
confidence: 99%